Predictors of deranged SPO2 and hypoglycaemia in neonates to assess neonatal survival and outcome by Rewa scoring system - Minarey, Naikey; Gornale, Vinod Kumar; Gada, Sandeep; Singh, Jyoti; Singh, H. P. (International Journal of Contemporary Pediatrics, 2021)
Background: Early referral to proper level of neonatal care is vital for neonatal survival. Deranged physiological status studied at the time of admission can be predictive of neonatal outcome. The present study was done in an attempt to discover statistically significant, more objective and feasible variables easily assessable by simple low cost devices for identification of sick newborns in need of stabilization and referral to tertiary facility based care. Primary objective was to study predictors of deranged neonatal percentage saturation of oxygen in blood as well as for neonatal hypoglycemia. Secondary objective was to develop a scoring system comprising of both subjective and objective variables to assess neonatal outcome. Methods: It was a prospective cohort observational study conducted at outborn neonatal intensive care unit in a tertiary level care hospital in Central India. Participants were all outborn neonates of age less than or equal to 28 days from March 2013 to May 2013 admitted in NICU. Results: A significant association was found between percentage saturation of oxygen in blood (SpO2) and other deranged neonatal pathophysiological variables i.e. hypothermia (p=0.001); delayed CRT (p=0.001); gestational age (p=0.002); cyanosis (p=0.003); respiratory distress (p=0.001). On applying multivariate binary logistic regression, hypothermia was found to be an important predictor of hypoglycaemia. The survival percentage was 91.5%, 87.7%, 76.5% and 20% with the scores of less than 5, score 6-10, score 11-16 and score >16 respectively. Conclusions: The scoring system based on both subjective and objective predictors is useful for timely identification and early referral of high risk neonates from primary and secondary level care to higher level. A high score predicts a poor outcome.